The Triumph of Ruler: Islam and Statecraft in Pre-Colonial Malay-Archipelago - Burhanudin, Jajat (Al-Jamiah Research Centre, 2017)
Taking pre-colonial period as the subject of study, this article argues that Islam is part of Malay culture and politics. Islam strongly engaged in the formation of Malay kingdoms, mingled with maritime commerce, and contributed to the formulation of Malay ideas of power and political management. Yet, it should be noted that the important role of Islam is to be explained by the fact that the religion gave emphasis to the idea of omnipotent ruler (raja), as was expressed in the Islamized language of politics, such as khalifa (vicegerent) and zill Allah fi al-alam (the shadow of Allah on earth). It was the ruler, with Islamic honorific titles and attributes, which appeared as the most determinant actor in the statecraft of kingdoms. Being as such, Islam could not be conceived of as an evaluation for rulersâ political conduct. Instead, Islam served as a religious justification for the rise of the absolutist kingdom of the archipelago, which culminated in the kingdom of Aceh in the seventeenth century.The ruler had paramount position over the subjects (rakyat) and the economic elites (orang kaya). [Artikel ini menjelaskan bahwa pada periode pra-kolonial, Islam merupakan bagian dari kebudayaan dan politik Melayu. Islam sangat berpengaruh dalam struktur kerajaan Melayu, campur tangan perdagangan laut, dan berperan dalam pembentukan konsep kekuasaan kerajaan Melayu dan manajemen politiknya. Tetapi perlu digarisbawahi bahwa peran penting Islam secara faktual adalah agama memberikan penekanan pada konsep raja yang dalam bahasa Islam politik disebut dengan khalifa dan zill Allah fi al-alam (wakil Tuhan di bumi). Sang raja, sebagaimana gelar dalam Islam, merupakan tokoh yang paling berkuasa dalam pemerintahan sebuah kerajaan. Sebagaimana yang terjadi, Islam tidak dapat diterima begitu saja sebagai koreksi terhadap perilaku politik sang raja. Alih â alih Islam justru menjadi justifikasi agama untuk kekuasaan mutlak raja, dimana puncaknya terjadi pada Kerajaan Aceh abad 17. Raja mempunyai kedudukan paling atas melampaui rakyat dan kaum borjuis.]Â